Eating disorders in the preoperative phase of bariatric surgery - Shirley Kelly dos Santos Simões; Renata Maria Gonçalves Pedrosa; Cinthia Katiane Martins Calado; Poliana Coelho Cabral; Regiane Maio; Maria Flora Correia; Maria Goretti Pessoa de Araujo Burgos (Medicina, 2022)
Introduction: Bariatric surgery is considered the most effective obesity treatment. Obese patients have a high prevalence of eating disorders. Objectives:  Evaluate the occurrence of eating disorders and eating patterns in candidates for bariatric surgery and associate eating disorders with sociodemographic and clinical characteristics. Methods: A retrospective study was conducted using electronic charts of candidates for bariatric surgery. Data were collected on sex, age, marital status, schooling, occupation, non-communicable diseases, body mass index (BMI), eating disorders, and eating patterns. Results: Among the 281 patients evaluated, eating disorders were detected in 26.7%; 10.3% had binge eating disorder, 6.6% had bulimia nervosa, and 5.3% had the night-eating syndrome. The specific eating patterns were overeating (46.6%), binge eating during periods of stress (9.3%), eating sweets (4%), and snaking (1.3%). BMI ranged from 35.38 to 59.03 kg/m² (mean: 44.37 ± 5.89). All individuals (100%) had systemic arterial hypertension, and 23.3% had type 2 diabetes mellitus or dyslipidemia. Conclusions: The frequency of eating disorders was low in the sample studied, the most common of which was binge eating disorder. Non-communicable diseases were associated with eating disorders. Among the eating patterns observed, the most frequent was overeating.